Cyanine‐Like Dyes with Large Bond‐Length Alternation. Issue 31 (20th June 2013) - Thorley, Karl J.; Hales, Joel M.; Kim, Hyeongeu; Ohira, Shino; Brédas, Jean‐Luc; Perry, Joseph W.; Anderson, Harry L.
Abstract Herein, the synthesis and properties of alkyne‐bridged carbocations, which are analogous in structure to cyanine dyes, are reported. An alkene‐bridged dye, linked at the third position of the indole, was also synthesized as a reference compound. These new carbocations are stable under ambient conditions, allowing characterization by UV/Vis and NMR (1H and 13C) spectroscopies. These techniques revealed a large degree of delocalization of the positive charge, similar to a previously reported porphyrin carbocation. The linear and nonlinear optical properties are compared with cyanine dyes and triarylmethyl cations, to investigate the effects of the bond‐length alternation and the overall molecular geometry. The value of Re(γ), the real part of the third‐order microscopic polarizability, of −1.3×10−33 esu for the alkyne‐linked cation is comparable to that of a cyanine dye of similar length. Nondegenerate two‐photon absorption spectra showed that the alkene‐bridged dye exhibited characteristics of cyanines, whereas the alkyne‐bridged dye is reminiscent of octupolar chromophores, such as the triarylmethyl carbocation brilliant green. Such attributes were confirmed and rationalized by quantum chemical calculations.